Pilot Study on the Effects of Aerobic and Resistance Exercise on Glucose Metabolism and Gut Microbiota in Older Adults with Type 2 Diabetes Mellitus - Yu, Hanglin; Tian, Haodong; Li, Hansen; Liu, Haowei; Peng, Li (Quality in Sport, 2025)
BACKGROUND: Physical exercise has a regulatory effect on intestinal flora and glucose metabolism, but the effect of aerobic combined resistance exercise on intestinal flora and glucose metabolism in patients with T2DM is unclear, so this paper will investigate the effect of aerobic combined resistance exercise on glucose metabolism and intestinal flora in patients with T2DM. METHODS: Twelve patients with T2DM were recruited, 4 were shed, and 8 were finally available, and aerobic combined Resistance exercise intervention was carried out on the patients for a period of 6 weeks, 3 times per week, and fasting blood and fecal samples were collected from the subjects before and after the intervention, and glucose metabolism indexes were detected on the blood samples, and intestinal flora was detected on the fecal samples, and the changes in glucose metabolism indexes and intestinal flora indexes of the patients with type 2 diabetes mellitus were compared before and after the intervention Results. RESULTS: (1) GSP in blood indexes was significantly reduced (t=9.07, P<0.05); (2) Alpha diversity analysis showed that the diversity of intestinal flora communities community coverage decreased significantly (P < 0.05). (3)The Venn diagram shows an increase in the number of intestinal flora species by 58, with a significant increase in the abundance of Agathobacter in the thick-walled portal (P<0.05). Conclusion: Aerobic combined with Resistance exercise intervention significantly improved GSP levels and increased beneficial intestinal flora and bacterial stability in T2DM patients. The study also found that Agathobacter increased with the decrease of FINS, and the genus showed a significant negative correlation with glucose metabolism indexes, which provides an important reference for the research of T2DM exercise intervention.